Determinants of obesity and overweight among school children of Pune city, Maharashtra, India: a cross sectional study - Ghonge, Swati; Bhambhani, G.D.; Adhav, P. S.; Thakor, Nilesh (International Journal of Research in Medical Sciences, 2017)
Background: Obesity is associated with an increased risk of morbidity and mortality as well as reduced life expectancy. The last two decade of previous century have witnessed dramatic increase in health care cost due to obesity and related issues among children and adolescents.The main objective of the study was to find out determinants of obesity and overweight among school children. Methods: The present cross sectional study was undertaken during July 2009 to April 2011 in randomly selected 4 schools of Pune city, India. Total 1281 children between the age group of 10 to 15 years were examined after taking written informed consent of their parents using pre-designed, pre-tested, semi-structured performa. Anthropometric measurements were taken and BMI were calculated. The prevalence of overweight and obesity were determined based on the IOTF (International Obesity Task Force) criteria. Various determinants of obesity and overweight were studied by interviewing children. Thus collected data was analyzed using Microsoft Excel and Open- Epi Software (Version 2.3). Results: Out of 1281 children, 54.09% were males. Overall prevalence of obesity and overweight was 5.62% and 9.99% respectively. The prevalence of obesity and overweight was significantly higher amongst less active group (9.3 % and 13.95%, respectively) as compared to more active group. Prevalence of obesity and overweight was significantly higher in the group of children who spent >3 hours for study and who spent >2 hours daily in front of television or computers. The prevalence of obesity and overweight was significantly higher amongst group of children who took daily calories above RDA (18.57% and 15.19% , respectively) as compared to the other group. The prevalence of obesity and overweight was significantly higher in them (8.91% and 13.36%) as compared to those who took junk food less than or equal to 2 times per week (1.71% and 5.98%,respectively). The prevalence of obesity and overweight among children having parents with history of obesity was 46.15% and 17.94%, respectively which was significantly higher than those without parental history of obesity (4.34% and 9.74%). Conclusions: The prevalence of obesity and overweight was significantly higher in children with sedentary lifestyle, high consumption of junk food and high calorie diet with positive family history of obesity.